Reluctance in writing wasiyyah among muslim in Malaysia / Suriana Ahmad Puat - Puat, Suriana Ahmad (Faculty of Business Management, 2018)
In Islamic inheritance system it is usually discussed about the framework of Faraid (Islamic Law of inheritance), Wasiyyah (Islamic Will) and Hibah (gift). For wasiyyah, it is limited up to one-third of the asset value for the non-heirs whereas the other twothird of wealth is transferred to the deceased's heirs by using the Faraid. However the data had shown that number of people who doing wasiyyah is very low. As mentioned in Utusan Malaysian news, it is estimated that only ten percent of people are having the wasiyyah. Thus, this shows that many Muslim are not concern in writing the wasiyyah. As reported by Deputy Minister of Natural Resources and Environment, Datuk Ir. Hanim in Utusan Malaysia news March 2016, the data has shown that there are around 60 billion of assets are not claimed by the heirs. This statistic are predicted to be increase every year. Therefore, at this scenario, it ffiggers the researchers to explore issues related to reluctance in writing wasiyyah. The purpose of this study is to identify which factors is actually contribute to reluctance in writing wasiyyah. This study had tested the factors such as knowledge, attitude, perception, organization and subjective norms. The data gathered had been analysed using the descriptive analysis, reliability test, correlation analysis and multiple regression to generate the result. Based on the result, only two variables had a significant relationship on reluctance in writing wasiyyah which are attitude and perception.